2001
DOI: 10.1002/j.1556-6676.2001.tb01996.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Three Measures of Multicultural Competency

Abstract: The purpose of this study was to examine the reliability and validity of 3 measures of multicultural competency, the Multicultural Counseling Awareness Scale: Form B (MCAS), the Multicultural Awareness‐Knowledge‐and‐Skills Survey (MAKSS), and the Survey of Graduate Students' Experiences with Diversity (GSEDS). Data were collected from 120 master's‐level students from counseling programs accredited by the Council for Accreditation of Counseling and Related Educational Programs or the equivalent. The findings ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 16 publications
5
36
1
1
Order By: Relevance
“…When considered, the multicultural competencies of counselors are generally viewed through the domains of knowledge, skills, and awareness (Dunn, Smith, & Montoya, 2006;Holcomb-McCoy & Day-Vines, 2004;Kocarek et al, 2001;Penderson, 1991;Pope-Davis & Dings, 1994;Sue et al, 1992). However, contradictory to previous research, data from the current research suggest that school counselors should have competence in ( Relationships.…”
Section: Instrument Developmentcontrasting
confidence: 61%
See 4 more Smart Citations
“…When considered, the multicultural competencies of counselors are generally viewed through the domains of knowledge, skills, and awareness (Dunn, Smith, & Montoya, 2006;Holcomb-McCoy & Day-Vines, 2004;Kocarek et al, 2001;Penderson, 1991;Pope-Davis & Dings, 1994;Sue et al, 1992). However, contradictory to previous research, data from the current research suggest that school counselors should have competence in ( Relationships.…”
Section: Instrument Developmentcontrasting
confidence: 61%
“…Currently, in the field of multicultural research, the most commonly used domains to assess multicultural competencies are knowledge, skills, and awareness (Dunn, Smith, & Montoya, 2006;Holcomb-McCoy & DayVines, 2004;Kocarek et al, 2001;Penderson, 1991;Pope-Davie & Dings, 1994;Sue et al, 1992). Contrasting these three presented domains, data from the qualitative research and the exploratory factor analysis suggested that the multicultural competencies for school counselors can be divided into four domains, including ( Based on the analyses run with the newly constructed instrument, school counselors generally reported being multiculturally competent on all four domains.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations